2008
DOI: 10.1542/peds.2006-3470
|View full text |Cite
|
Sign up to set email alerts
|

Experiences of Parents Who Have Children With Chronic Kidney Disease: A Systematic Review of Qualitative Studies

Abstract: In addition to "normal" parental roles, being a parent of a child with chronic kidney disease demands a high-level health care provider, problem solving, information seeking, and financial and practical skills at a time when the capacity to cope is threatened by physical tiredness, uncertainty, and disruption to peer support within and outside the family structure. Parents of children with chronic kidney disease need multidisciplinary care, which may lead to improved outcomes for their children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

9
171
1
15

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 191 publications
(196 citation statements)
references
References 40 publications
9
171
1
15
Order By: Relevance
“…Increasing numbers of adolescents with life-threatening conditions are surviving into adulthood, and consequently more of them will experience the transfer from paediatric to adult care (Rutishauser et al, 2011, Tong et al, 2008. The prevalence of chronic conditions in adolescence ranges from 7% to 15% (Michaud et al, 2004), and transition to adult care has thus become an important issue (Bell and Sawyer, 2010, Hersh et al, 2009, Tuchman et al, 2010.…”
Section: Introductionmentioning
confidence: 99%
“…Increasing numbers of adolescents with life-threatening conditions are surviving into adulthood, and consequently more of them will experience the transfer from paediatric to adult care (Rutishauser et al, 2011, Tong et al, 2008. The prevalence of chronic conditions in adolescence ranges from 7% to 15% (Michaud et al, 2004), and transition to adult care has thus become an important issue (Bell and Sawyer, 2010, Hersh et al, 2009, Tuchman et al, 2010.…”
Section: Introductionmentioning
confidence: 99%
“…Enough reports have been published to emphasise that being a parent of a child with CKD demands a high level healthcare provider who has to balance problem solving and information gathering with financial and practical skills at a time when physical tiredness and disrupted peer and family support may prevail [14,15]. A systematic review of 16 qualitative studies on the experiences of parents grouped ten themes into three clusters-intrapersonal (living with constant uncertainty, stress and maintaining vigilance despite fatigue), interpersonal (medicalisation of the parental role, dependence and conflict with staff and disrupted peer relationships) and external issues (management of the medical regimen, transportation, finances, diet restrictions and balancing medical care with domestic responsibilities) [14].…”
Section: Introductionmentioning
confidence: 99%
“…A systematic review of 16 qualitative studies on the experiences of parents grouped ten themes into three clusters-intrapersonal (living with constant uncertainty, stress and maintaining vigilance despite fatigue), interpersonal (medicalisation of the parental role, dependence and conflict with staff and disrupted peer relationships) and external issues (management of the medical regimen, transportation, finances, diet restrictions and balancing medical care with domestic responsibilities) [14]. A recent study report from Taiwan showed that depression was significantly more common in caretakers of children on chronic peritoneal dialysis (CPD) compared with controls, with a much lower annual income, higher under-employment and single parent rates in the study group [16].…”
Section: Introductionmentioning
confidence: 99%
“…Due to complicated medication schedules, nutritional restrictions, and procedures such as hemo-or peritoneal dialysis, the care for their children is complex [1]. Complications such as infections, bone disease and kidney failure are frequently seen [1,2].…”
Section: Introductionmentioning
confidence: 99%
“…Due to complicated medication schedules, nutritional restrictions, and procedures such as hemo-or peritoneal dialysis, the care for their children is complex [1]. Complications such as infections, bone disease and kidney failure are frequently seen [1,2]. Additionally, parents experience difficulties in balancing the needs of their sick child with their own responsibilities, such as other children, family members, work, and social life [3].…”
Section: Introductionmentioning
confidence: 99%